2018
DOI: 10.1108/cg-09-2017-0208
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and firm value: a comparative analysis of state and non-state owned companies in the context of Pakistan

Abstract: Purpose The purpose of this paper is to examine how corporate governance instruments impact firm value in the context of Pakistan. This paper considers state- and non-state-owned enterprises and examines whether the influence of corporate governance on firm value varies across firms having different nature of ownership. Design/methodology/approach This study opts for an unbalanced sample of state- and non-state-owned enterprises for the period 2010-2014. Panel data regression is adopted for estimation of mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
64
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 35 publications
17
64
1
6
Order By: Relevance
“…Increased added value for investors is created by applying the principles of information disclosure, accountability, responsibility, independence, and equality and fairness. The results of this study found that good corporate governance has a positive effect on company value, thereby supporting research conducted by Ammann et al (2011);Baek, Kang, & Suh Park, (2004); Bhat et al (2018). The results of hypothesis testing prove good corporate governance moderates the effect of tax planning on firm value.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Increased added value for investors is created by applying the principles of information disclosure, accountability, responsibility, independence, and equality and fairness. The results of this study found that good corporate governance has a positive effect on company value, thereby supporting research conducted by Ammann et al (2011);Baek, Kang, & Suh Park, (2004); Bhat et al (2018). The results of hypothesis testing prove good corporate governance moderates the effect of tax planning on firm value.…”
Section: Resultssupporting
confidence: 82%
“…Increased added value for investors is created by applying the principles of information disclosure, accountability, responsibility, independence, and equality and fairness. Previous research found the level of implementation of good corporate governance has a positive effect on firm value (Ammann, Oesch, & Schmid, 2011;Bhat, Chen, Jebran, & Bhutto, 2018). Based on agency theory and the results of empirical research on the direction of good corporate governance on corporate value, the following hypothesis can be formulated.…”
Section: Introductionmentioning
confidence: 99%
“…In the agency theory perspective, boards play an important role in preventing decisions that are not aligned with the residual claimants' interests (Fama and Jensen;1983). Boards with improved structure and a higher proportion of independent members can exercise better monitoring, and thereby reduce agency conflicts (Bhat et al;. Black et al (2020) explain that an improvement in board structure, aligned with improved disclosure, can have an impact on a firm's market value since expected cash flows to minority shareholders are increased.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is a lack of studies on which specific aspects of corporate governance (such as board attributes) are associated with firm value (Black et al;2020). Board attributes, such as independence, can lead to higher firm value and performance by reducing agency conflicts (Bhat et al;. Therefore, it is important to understand the relation between corporate governance mechanisms and performance to develop proper corporate and public policies (Kao et al;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation